A Case of Severe Valgus Knee with Rheumatoid Arthritis - HATTORI Daiya; 三井 忠夫; 宮本 浩秀; 木全 則文; 川島 正幹; 青山 効司; 岩堀 裕介; 佐藤 啓二 (Japanese Journal of Rheumatism and Joint Surgery, 2005)
An RA patient with a severely valgus knee was treated with total knee arthroplasty (using a Nexgen LCCK) . The patient was a woman aged 77 years. Pre-and postoperative axial alignments were measured on weight-bearing long-standing radiographs. Clinical data summarized using the Japan Orthopaedic Association score (JOA score) . The f emoro-tibial angle (FTA) was 145°preoperatively and 175°postoperatively. The preoperative flexion angle was 90°and the postoperative flexion angle was 120°. The preoperative JOA score was 26 points and the postoperative JOA score was 61 points. The patient was satisfied with the results of the operation.